Ritualstruktur og ritualklassifikation - Schjødt, Jens Peter (Religionsvidenskabeligt Tidsskrift, 1992)
The purpose of this article has been to evaluate some major contributions in the study of ritual in order to reach some strategy, according to which it will be possible to describe and classify the different categories of rituals. It is suggested that the description of the structure must include both the horizontal structure as investigated by van Gennep and the vertical including the opposition between liminal and non-liminal ritual space, as this has been outlined by Victor Turner. As to the classification it is proposed that the only structural criteria to match the functional division of rites of passage, calendrical rites and crisis rites is the relation between the quality of the level of the initial and the final phases.